2019
DOI: 10.1093/nutrit/nuz050
|View full text |Cite
|
Sign up to set email alerts
|

Effects of soy isoflavones on cognitive function: a systematic review and meta-analysis of randomized controlled trials

Abstract: Context The results of preclinical and observational studies support the beneficial effect of soy isoflavones on cognition. Objective This review aimed to evaluate the effects of soy isoflavones on cognition in adults. Data Sources The PUBMED, EMBASE, Ovid Medline, Cochrane Library, and clinicaltrials.gov databases were searched. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 76 publications
1
42
0
Order By: Relevance
“…Some of that enthusiasm faded as subsequently published research produced equivocal findings (Balk et al 2005). Nevertheless, research into the benefits of soy and isoflavoneswith results often supportive of efficacycontinue to be published at an impressive rate (Man et al 2021;Sansai et al 2020;Cui et al 2020;). However, concerns about the safety of isoflavones have led to these soybean constituents, and as a result, to soyfoods, becoming controversial.…”
Section: Discussionmentioning
confidence: 99%
“…Some of that enthusiasm faded as subsequently published research produced equivocal findings (Balk et al 2005). Nevertheless, research into the benefits of soy and isoflavoneswith results often supportive of efficacycontinue to be published at an impressive rate (Man et al 2021;Sansai et al 2020;Cui et al 2020;). However, concerns about the safety of isoflavones have led to these soybean constituents, and as a result, to soyfoods, becoming controversial.…”
Section: Discussionmentioning
confidence: 99%
“…These (poly)phenol compounds (i.e., flavones, flavonols, isoflavones, flavanones/flavanonols, flavanols, and anthocyanidins) are present in high amounts in fruits, vegetables, and natural products such as parsley, celery, onions, leeks, broccoli, soy, oregano herbs, green tea, red wine, citrus fruit, berry fruits, and dark chocolate [20,21]. Although research has historically focused on antioxidant properties [22][23][24][25], recent data from randomized placebo-controlled trials suggest (poly)phenols may also modulate neurological disorders, cerebral hypoperfusion, and neuroinflammation while simultaneously enhancing memory, learning, and cognitive performances in old-aged adults [19,[26][27][28][29][30][31][32][33][34]. Mastroiacovo et al [26] demonstrated a daily consumption of 250 mL Cocoa drinks, with a high flavanol content (993 mg), for 8 weeks has the potential to improve psychomotor performance, verbal fluency performance, as well as the overall cognitive performance (i.e., z-score).…”
Section: Introductionmentioning
confidence: 99%
“…The inverse association between DHA and Aβ may be attributed to the fact that DHA suppresses Aβ production [ 42 ] and promotes Aβ clearance [ 43 ]. Regarding soy isoflavones, we and others reported that supplementation of soy isoflavones improved cognitive function, especially in the memory domains, based on evidence from the systematic review and meta-analysis of randomized controlled trials (RCTs) [ 44 , 45 ]. In addition, our systematic review and meta-analysis of RCTs found that supplementation of soy isoflavones reduced arterial stiffness [ 46 ].…”
Section: Discussionmentioning
confidence: 99%